Leadership Strategies and Policies on Online Learning during the Covid-19 Pandemic: A Case Study - Marzul Hidayat; Rudi Hartono (Indonesian Research Journal in Education |IRJE|, 2021)
Educational institutions around the world have closed due to the COVID-19 pandemic endangering the academic agendas. Educational institutions have to shift to online learning platforms to keep the educational activities working. Nonetheless, the questions about the educational leadership strategies and policies of online learning are not clearly understood yet, principally for a developing country like Indonesia, where the technical constrictions like access to the Internet have become a serious issue. In this study, we focused on finding out the leadership strategies and policies of the heads of the postgraduate study programs and looking at the entire cycle in the learning process by looking at the implementation and evaluation of the goals of online learning during the pandemic. The study design was qualitative in the case study approach. Seven participants were willing to get involved in this study. The primary data sources were in-depth interviews with seven participants who are the heads and secretary of the postgraduate program at one public university in Jambi. We examined our interviews data by using within-case and cross-case displays and analyses. We categorized our analysis and discussion about our participants’ perspectives and the contexts in which leadership strategies and policies of online learning they managed emerge. The analysis of our texts revealed that major issues related to the causes and covid-19: the rapid, unpredictable and 'forced' transition from face-to-face teaching to distance or online teaching, leadership strategies and policies in online learning, and evaluating teaching and learning processes: “assessing its achievements and improving upon its effectiveness.” Future education research and implications are also discussed.